(3hGLHGJ GdUdGI QSGdI PcQ ajgG hGLHGJ GdUdGI eMTjG HgG Ydi GdOQ GdeNJGQs - (3GdRjdYj, GdLHQJj, GdYbjdj, GdMfaj, MSf Hf EHQGgje Hf MSf, J (B1188(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdhGLH GdhLhO GdeajV Ydi Ndbg ehGgH GdEMSGf(B...(3ajbhd GdabjQ Edi dWa QHg GdNaj MSf(B...(3bO hbY aj YHGQI GdOQ GdeNJGQ TQM JfhjQ GdCHUGQ(B...s
(3BNQgG (B:s
...(3CfgG ef GdaGJMI HNHQ GdhGMO dcfg jhLH GdYed aUGQJ efgG YedG aef dReg bQGAI GdaGJMI dReJg GdJSejI GMJjGWG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B178s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B531s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis